Effect of interrepetition rest intervals on weight training repetition power output - Lawton, T. M.; Cronin, J.; Lindsell, R. (The Journal of Strength and Conditioning Research, 2006)
The purpose of this study was to determine the change in weight training repetition power output as a consequence of interrepetition rest intervals. Twenty-six elite junior male basketball and soccer players performed bench presses using a 6 repetition maximum (6RM) load. The power output for each repetition was recorded using a linear encoder sampling each 10 ms (100 Hz). Subjects were assigned to 1 of 3 intervention groups, differentiated by the arrangement of rest intervals within the 6 repetitions: 6 × 1 repetition with 20-second rest periods between each repetition (Singles); 3 × 2 repetitions with 50 seconds between each pair of repetitions (Doubles); or 2 × 3 repetitions with 100 seconds of rest between each 3 repetitions (Triples). A timer was used to ensure that the rest interval and duration to complete all interrepetition interventions was equated across groups (118 seconds). Significantly (p < 0.05) greater repetition power outputs (25-49%) were observed in the later repetitions (4-6) of the Singles, Doubles, and Triples loading schemes. Significantly greater total power output (21.6-25.1%) was observed for all interrepetition rest interventions when compared to traditional continuous 6RM total power output. No significant between-group differences were found (p = 0.96). We conclude that utilizing interrepetition rest intervals enables greater repetition and total power output in comparison to traditional loading parameters.